The Power of Two: Inclusive Growth and the IMF - Prakash Loungani (Intereconomics, 2017)
For decades, mainstream economics has focused on increasing economic growth and accelerating cross-country convergence, while ignoring distributional concerns. However, the consensus has begun to shift, and recent IMF research has paid increased attention to inclusive growth and the detrimental macroeconomic effects of inequality. The IMF also recognises the threat posed by climate change and has begun to dedicate research to exploring ways to decouple carbon emissions from economic growth.
Keywords: 330